Mushrooms and other fungi of the midcontinental United States - Huffman, D. M. (Donald M.), 1929-2014; Huffman, D. M. (Donald M.), 1929-2014 (Bur Oak guide., 2008)
This completely revised second edition provides all the information necessary to identify mushrooms in the field in the midcontinental region of Iowa, Illinois, Nebraska, Missouri, Minnesota, South Dakota, and Wisconsin: the tallgrass prairies and the western parts of the eastern deciduous forests.